Bioactive Compounds from Endophytic Bacteria Bacillus subtilis Strain EP1 with Their Antibacterial Activities - Muhammad Numan; Muddaser Shah; Sajjad Asaf; Najeeb Ur Rehman; Ahmed Al-Harrasi (Metabolites, 2022)
Endophytic bacteria boost host plant defense and growth by producing vital compounds. In the current study, a bacterial strain was isolated from the Boswellia sacra plant and identified as Bacillus subtilis strain EP1 (accession number: MT256301) through 16S RNA gene sequencing. From the identified bacteria, four compounds—1 (4-(4-cinnamoyloxy)phenyl)butanoic acid), 2 (cyclo-(L-Pro-D-Tyr)), 3 (cyclo-(L-Val-L-Phe)), and 4 (cyclo-(L-Pro-L-Val))—were isolated and characterized by 1D and 2D NMR and mass spectroscopy. Moreover, antibacterial activity and beta-lactam-producing gene inhibition (δ-(l-α-aminoadipyl)-l-cysteinyl-d-valine synthetase (ACVS) and aminoadipate aminotransferase (AADAT)) assays were performed. Significant antibacterial activity was observed against the human pathogenic bacterial strains (E. coli) by compound 4 with a 13 ± 0.7 mm zone of inhibition (ZOI), followed by compound 1 having an 11 ± 0.7 mm ZOI. In contrast, the least antibacterial activity among the tested samples was offered by compound 2 with a 10 ± 0.9 mm ZOI compared to the standard (26 ± 1.2 mm). Similarly, the molecular analysis of beta-lactam inhibition determined that compounds 3 and 4 inhibited the two genes (2- to 4-fold) in the beta-lactam biosynthesis (ACVS and AADAT) pathway. From these results, it can be concluded that future research on these compounds could lead to the inhibition of antibiotic-resistant pathogenic bacterial strains.